TRANSLATION STRATEGIES FOR TRANSLATING A NEWS ARTICLE - Junining, Esti; Kusuma, Vidi A.M.C (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2020)
There are various kinds of translation strategies proposed by the experts of translation. This study aims to find out the translation strategies used by the English Education students from Faculty of Cultural Studies (FCS) of Universitas Brawijaya (UB) in translating a news article. The translation strategies used by the students are categorized based on the Baker's taxonomy. The result shows that the students employ all of the eight translation strategies from Baker's taxonomy in translating the news article. The three most used translation strategies are translation by using a more general word (95%), paraphrasing using related words (75%), cultural submission and omission (73%). On the contrary, the least used translation strategy is translation by illustration (31%). From the result of the study, it is suggested that researchers interested in translation can conduct more research about the students' translation in a deeper and more specific analysis.